RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN PESERTA DIDIK BARU (PPDB) ONLINE DAN CONTENT MANAGEMENT SYSTEM (CMS) SEKOLAH BERBASIS WEB DI SDN NGARGOTIRTO 4 - Distan Budi Utomo; Sri Handayani; Yudhistiro Pandu Widhoyoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology demands educational institutions to adapt to provide better community services. SDN Ngargotirto 4 currently faces administrative challenges as the New Student Admission (PPDB) process is still conducted manually using paper forms. This conventional method causes long queues, data redundancy, physical document damage, and requires extensive time for data recap. Furthermore, the school lacks an official digital media platform to publish academic achievements and announcements, limiting its public visibility. This research aims to design and develop a web-based integrated information system combining an online PPDB module and a Content Management System (CMS). The development utilizes PHP Native to ensure a lightweight and highly controllable system architecture without relying on heavy frameworks, combined with a MySQL database for secure relational data management. The user interface is built using HTML, CSS, JavaScript, and Bootstrap to achieve a responsive web design accessible via smartphones and computers. Testing is conducted in a local server environment using Laragon. The result of this system design is expected to streamline the admission process, eliminate physical paperwork, and provide an independent, user-friendly platform for school operators to update information continuously, thereby improving the school's digital branding and public transparency.